Ответ:
(cos(a)^2+cos(a)^4=cos(a)^6)/3+sin(a)^4
Объяснение:
(1+cos(a)^2=cos(a)^4xcos(a)^2)/3+sin(a)^4 - Вычислить произведение
((1+cos(a)^2+cos(a)^4)xcos(a)^2)/3+sin(a)^4 - Раскрыть скобки, выполнив умножение на cos(a)^2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(cos(a)^2+cos(a)^4=cos(a)^6)/3+sin(a)^4
Объяснение:
(1+cos(a)^2=cos(a)^4xcos(a)^2)/3+sin(a)^4 - Вычислить произведение
((1+cos(a)^2+cos(a)^4)xcos(a)^2)/3+sin(a)^4 - Раскрыть скобки, выполнив умножение на cos(a)^2